Importancia de la facultad recaudadora en la gestión de la administración tributaria. - Cuenca Minta, Nancy Rocio (My University, 2018)
The purpose of the research work is to determine the importance of the collection authority in the Tax Administration Management in Ecuador, giving the authority to take collection actions to reduce tax evasion that damages the tax revenue, since these are used to the socio-economic development of the country. The collection authority is considered as the last stage that the taxpayer performs or responsible for compliance with the tax obligation of the voluntary payment to the Tax Administration, in order to ensure an efficient, transparent and efficient collection for the good of the Ecuadorian State. The Tax Administration seeks to increase the collection of taxes with the good practices of the principles with the duties and attributions in accordance with the law for the correct fulfillment of their declarations of the real income that come from licitas activity for the payment of correct values of way voluntary The methodology used in this investigation was based on documentary and bibliographic analysis of statistical information on collection of the Internal Revenue Service, as well as on scientific articles and legal bases such as the Tax Code, the Internal Tax Regime Law and the Constitution. Obtaining as a result of tax collection an increase in the payment of the different taxes according to their nature in order to improve the tax income to the contribution to the Treasury since that helps investment, reinvestment in social progress and a better distribution of national income.
El trabajo de investigación tiene como finalidad determinar la importancia que ejerce la facultad recaudadora en la Gestión de Administración Tributaria en el Ecuador dando la potestad de tomar acciones de cobro para disminuir la evasión de impuesto que perjudica al ingreso fiscal, ya que estos son utilizados para el desarrollo socio-económico del país. La facultad recaudadora es considerada como la última etapa que realiza el contribuyente o responsables ante el cumplimiento de la obligación tributaria del pago voluntario a la Administración Tributaria, con fines de asegurar una recaudación eficiente, transparente y eficaz en bien del Estado Ecuatoriano. La Administración Tributaria busca incrementar el cobro de impuestos con las buenas prácticas de los principios con los deberes y atribuciones de conformidad con la ley para el cumplimiento correcto de sus declaraciones de los ingresos reales que procedan de actividad licitas para el pago de valores correctos de manera voluntaria. La metodología que se utilizó en esta investigación fue base en análisis documental y bibliográfico de información estadística de recaudación del Servicio de Rentas Internas, así como en artículos científicos y bases legales como el Código Tributario, Ley de Régimen Tributario Interno y la Constitución. Obteniendo como resultado de la recaudación de tributos un incremento en el pago de los distintos impuestos según sea su naturaleza con la finalidad de mejorar el ingreso tributario a la aportación para con el Fisco ya que eso ayuda a la inversión, reinversión en el progreso social y una mejor distribución de la renta nacional.
Keywords: FACULTAD RECAUDADORA; ADMINISTRACIÓN TRIBUTARIA; FISCO; CONTRIBUYENTE; EVASIÓN FISCAL